Conditional cooperation: Type stability across games - Michael Eichenseer; Johannes Moser (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2019)
In this paper, we use an experimental setup to classify cooperation types using a sequential prisoner's dilemma and a one shot sequential public goods game. In these two games, we examine the within subject stability of cooperation preferences. Our results suggest that subjects classified as conditional cooperators in the prisoner's dilemma match others' contributions in the public goods game to a significantly larger degree compared to other types, which indicates a substantial consistency. Regarding discrete behavioral types, we find that the prisoner's dilemma performs well in identifying conditional cooperators while it is only an imperfect tool for identifying selfish types in the public goods game.
Keywords: C72; C91; H41; 330; conditional cooperation; public goods game; sequential prisoner's dilemma; discrete behavioral types